Pengaruh Model Pembelajaran Realistic Methematic Education (RME) terhadap Hasil Belajar Matematika di Kelas VI SD Negeri 122332 Jl. Jend Sudirman Pematang Siantar - Aulya Briliantina Gaja; Minar Trisnawati Lumbantobing; Esti Siriat (Journal on Education, 2023)
This study aims to determine the effect of the Realistic Mathematics Education (RME) learning model on mathematics learning outcomes in class VI students at SD Negeri No.122332 Jl.Jend Sudirman Pematang Siantar. The type of research used by researchers is experimental research, namely the Quasi Experimental Design method which uses experimental research, namely Quasi Experimental Design type Nonequivalent Control Group Design. This research was conducted at SD Negeri 122332 Jl. Jend Sudirman, Pematang Siantar City in the even semester of the 2022/2023 Academic Year in April. The population of this study were all fourth grade students at SD Negeri 122332 Jl. Jend Sudirman with a total of 63 students. The sampling technique for this study was non-probability sampling, saturated sampling technique, namely class IV-A and class IV-B, the (experimental) group from class VI-A had 32 students and the (control) group from class IV-B had 31 students. person. The results of testing the research hypothesis have a significant influence on this study through the data that has been tested the data can be seen that the sig (2-tailed) value is 0.001 <0.05, this indicates that there is a significant difference.